Pengaruh Rasio Profitabilitas Terhadap Harga Saham Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia pada Tahun 2015 - 2021 - Muhidin Muhidin; Tiar Lina Situngkir (Transformasi Manageria: Journal of Islamic Education Management, 2023)
This study was conducted to determine the effect of return on assets, return on equity and earnings per share on stock prices of banking companies listed on the Indonesia Stock Exchange in 2015-2021. This study uses quantitative methods with verification approaches. The research sample amounted to 10 banking companies with a research period of 7 years taken using purposive sampling technique so that the number of data studied was 70 data. This study uses multiple linear regression analysis to determine the effect of the independent variable on the dependent variable either partially or simultaneously. The results of data analysis show that partially return on assets and earnings per share have an influence on stock prices. while return on equity has no effect on stock prices. Simultaneously return on assets, return on equity and earnings per share have an influence on stock prices of banking companies listed on the IDX in 2015-2021. Keywords: Return on Asset, Return on Equity, Earning per Share, Stock Price